MARGIN FEEDING DAMAGE ON THE LEAVES OF CONIFERS AND GINKGOALES FROM THE MESOZOIC OF TRANSBAIKALIA - Vasilenko D.V. (My University, 2006)
A new approach to the formal classification of arthropod margin feeding plant damage is proposed. Several types of margin feeding traces on the leaves of Pityophyllum sp. and Ginkgoites sp. from the Upper Jurassic-Lower Cretaceous Chernovskie Kopi locality, Transbaikalia, are described as five new species in the genus Pinovulnus gen. nov.
Keywords: Mesozoic::Jurassic; Мезозой::Юрская; Mesozoic::Cretaceous; Мезозой::Меловая